Instruments for the Evaluation Analysis of Performance and Risk in the Brazilian Stock Market: a study of the market anomalies at (BOVESPA) Sao Paulo - Pagnani, Eolo Marques; Olivieri, Francisco José (Review of Business Management, 2007)
As from the assumption of efficient markets, the discovery of the meaning of the relations among the assets negotiated in the Stock Exchange market and a certain standard of rational conduct, selected (representative) in the decision-making by the investors, this study aimed at developing the questionings arising from the Arbitrage Pricing Theory (APT) model, based on the Capital Asset Pricing Model (CAPM) of the pricing in portfolios, which relations among its components are translated by Beta. This study applies to the evolution of the evaluation theories, risk measurement and formation of assets’ prices (expected pay-back) which, in recent studies, have shown that, many times, the behavior of the investors does not confirm the divulged efficiency of the markets. The study was based on certain areas of the theory of investments, highlighting the risk approach as a factor for decision-making, in addition to the Asset Pricing Models of portfolios evaluation. This study was based on a documental and data research with the Sao Paulo Stock Exchange, institutions that manage investment funds and the Brazilian Central Bank (from 1997 to 2001) to test the several theories on market efficiency and, finally, the analysis of the information obtained from data modeling, searching to identify the consistency of the results, in view of the different models studied, relating them to the concepts of market weaknesses. As a result, it was possible to define the Security Market Line for the Brazilian market, based on the assets pricing models, beta coefficients and APT factors. Key-words: Securities market (stock exchange). Market weaknesses. Pricing models in portfolios.